2020
DOI: 10.1051/e3sconf/202017801017
|View full text |Cite
|
Sign up to set email alerts
|

The use of heat transformers for the low-temperature secondary energy resources recovery in non-ferrous metallurgy enterprises

Abstract: The paper discusses the concept of developing schemes for the utilization of low potential secondary energy resources waste heat in heat transformers (HT). There ara several examples of using HT in non-ferrous metallurgy plants in Russia and Kazakhstan: the production of nickel, zinc and ferroalloys. In the case of nickel production, two schemes are proposed for consideration: for summer and winter modes. The main object of study is a nickel production scheme using a lithium bromide absorption chiller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
1
0
8
Order By: Relevance
“…Таким образом, проект по применению теплового насоса НТ-3000 окупил себя за два с небольшим года [5][6][7][8][9]. В период 2000-2020 годы реализованы ряд проектов с применением ПКТН, использующих в качестве низкопотенциальных источников как сбросное тепло промышленных предприятий, канализационно-очистных сооружений, так и различные возобновляемые источники энергии (тепло грунтов, грунтовых вод) [5][6][7][8][9][10]14].…”
Section: результаты и обсуждениеunclassified
See 2 more Smart Citations
“…Таким образом, проект по применению теплового насоса НТ-3000 окупил себя за два с небольшим года [5][6][7][8][9]. В период 2000-2020 годы реализованы ряд проектов с применением ПКТН, использующих в качестве низкопотенциальных источников как сбросное тепло промышленных предприятий, канализационно-очистных сооружений, так и различные возобновляемые источники энергии (тепло грунтов, грунтовых вод) [5][6][7][8][9][10]14].…”
Section: результаты и обсуждениеunclassified
“…Исследования по применению ПКТН и разработка ТЭО проектов также проведены на таких крупных промышленных предприятиях Казахстана, как АО «АрселорМиттал Темиртау», АО «Алюминий Казахстана», АО «Экибастузская ГРЭС-2», АО «Усть-Каменогорская ТЭЦ», АО «Согринская ТЭЦ», АО ТЭЦ-2 г. Астаны, АО «ТЭЦ-2 г. Петропавловска», АО «Астана Су Арнасы», ТОО «KSP Steel», Аксуский завод ферросплавов и др. [5][6][7][8][9][10]14].…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…Integration of heat pump units in thermal schemes of manufactures leads to boosting heat generating capacities while not increasing consumption of primary fuel. Moreover, the same authors suggested some designs of the inclusion of absorption heat pumps to such an enterprise [34].…”
Section: Introductionmentioning
confidence: 99%
“…на энергоемких предприятиях всегда есть излишки тепловой энергии, которые необходимо утилизировать: горячая вода, пар, отходящие (дымовые) газы. Особое внимание следует уделять крупным отраслям, например, энергетике, нефтехимии, черной и цветной металлургии, где имеется значительное количество избыточного тепла в виде промышленных стоков или оборотных циклов [1][2][3][4][5][10][11][12].…”
Section: Introductionunclassified